2011
DOI: 10.1002/aqc.1245
|View full text |Cite
|
Sign up to set email alerts
|

Host‐specificity of the endangered thick‐shelled river mussel (Unio crassus, Philipsson 1788) and implications for conservation

Abstract: ABSTRACT1. The complex life cycle of the endangered thick-shelled river mussel (Unio crassus, Philipsson 1788) includes an obligatory parasitic phase on a host fish. Consequently, knowledge of the interaction of U. crassus with its host species is crucial for the development of effective conservation strategies.2. The objective of this study was to assess systematically the host suitability of eight different fish species, including six native species which naturally co-occur with U. crassus, as well as two no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
80
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 19 publications
2
80
0
1
Order By: Relevance
“…Previous studies on European Unio species supported this statement (Berrie and Boize 1985, Araujo et al 2005, Blažek and gelnar 2006, taeubert et al 2012a. Experimental infections with Unio crassus Philipsson, 1788 and Unio mancus lamarck, 1819 revealed that their glochidia can metamorphose successfully on a broad range of fish species from different genera (Hochwald and Bauer 1990, Araujo et al 2005, taeubert et al 2012a. However, glochidia from both species were found only in a restricted number of fish species in the wild (Engel and Wächtler 1989, Hochwald and Bauer 1990, Araujo et al 2005, taeubert et al 2012b, suggesting a more ecologically driven specific host-parasite relationship.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…Previous studies on European Unio species supported this statement (Berrie and Boize 1985, Araujo et al 2005, Blažek and gelnar 2006, taeubert et al 2012a. Experimental infections with Unio crassus Philipsson, 1788 and Unio mancus lamarck, 1819 revealed that their glochidia can metamorphose successfully on a broad range of fish species from different genera (Hochwald and Bauer 1990, Araujo et al 2005, taeubert et al 2012a. However, glochidia from both species were found only in a restricted number of fish species in the wild (Engel and Wächtler 1989, Hochwald and Bauer 1990, Araujo et al 2005, taeubert et al 2012b, suggesting a more ecologically driven specific host-parasite relationship.…”
mentioning
confidence: 64%
“…disCUssion Freshwater mussels belonging to the subfamily Unioninae sensu graf and cummings (2006) are known to present a generalist host-parasite relationship (Watters and o'dee 1998). Previous studies on European Unio species supported this statement (Berrie and Boize 1985, Araujo et al 2005, Blažek and gelnar 2006, taeubert et al 2012a. Experimental infections with Unio crassus Philipsson, 1788 and Unio mancus lamarck, 1819 revealed that their glochidia can metamorphose successfully on a broad range of fish species from different genera (Hochwald and Bauer 1990, Araujo et al 2005, taeubert et al 2012a.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Both species are therefore currently listed as Endangered on the IUCN Red List (IUCN, ) and protected under EU law (Annex II and Annex IV of the EU Habitats Directive for U. crassus ; Annex II and Annex V for M. margaritifera ). Despite their shared conservation status, these species differ substantially in their habitat requirements (Denic, Stoeckl, Gum, & Geist, ; Geist & Auerswald, ) and host use (Taeubert & Geist, ; Taeubert, Gum, & Geist, ). Margaritifera margaritifera is often considered as a habitat specialist.…”
Section: Introductionmentioning
confidence: 99%
“…A juvenile mussel's size also has an impact on recruitment, where a large juvenile has a higher chance of survival compared to a smaller sized mussel. One factor that regulates the condition and abundance of hatched juveniles is the host fish species (Arvidsson et al, 2012;Taeubert et al, 2012). Another factor that impacts the number of hatched juveniles may be the age of the host fish.…”
Section: Introductionmentioning
confidence: 99%